Implementation of Network Governance in the Development of Rendang Industries in Payakumbuh City - Zella Dyo, Berlian; Aromatica, Desna; Koeswara, Hendri (Indonesian Association for Public Administration (IAPA), 2023)
Regional Technical Implementation Unit of Rendang Service and Development Center still faces obstacles in efforts to develop the Rendang Small and Medium Industry. So that coordination, integration, and synchronization with stakeholders from internal and external Payakumbuh City government are formed in a network governance. This paper aims to describe the implementation of network governance in the development of the Rendang Small and Medium Industry in Payakumbuh City. The author uses a descriptive qualitative approach to explain, record, and analyze data obtained from relevant literature studies. The phenomena found will be analyzed using network governance theory by Klijn and Koppenjan. The conclusion is that the implementation of network governance in the development of the Rendang Small and Medium Industry in Payakumbuh City has not run optimally due to unclear network management, despite the involvement and trust of stakeholders. This unclear network management has implications for achieving results that are not maximized. In general, the network formed has resulted in innovation, integrated solutions, contributions from stakeholders, problem-solving capacity, efficiency and support. However, it is still necessary to pay attention to indicators of resilience, conflict resolution, and network development due to poor network management.